Itinerários do bovarismo - Souza, Eliana Maria de Melo [UNESP] (My University, 2013)
According to Sérgio Buarque de Holanda, there is a “thinking addiction" in Brazil that disfigures reviews and creates disadvantages for a better understanding of the real changing of conditions in society. It is in Raízes do Brasil that this "reasoning addiction" is best defined as an "Invincible disenchantment from the view of our real conditions". This definition is supported by the bovarism theory - pouvoir qu`a l`homme de se concevoir autre qu’il n’est - theory formulated by Jules de Gaultier (1858-1942), French homme de lettres and who promoted Nietzsche in France - for this title, he is self intended as a philosopher, which extends the characterization of the individual drama of Flaubertian's character of Madame Bovary for the characterization of nations. Sérgio Buarque de Holanda is not the only author who uses this notion, before him, it was also in Paulo Prado and Lima Barreto and much after him in Celso Furtado and Paulo Eduardo Arantes, to keep with the best known authors. This article aims to show how bovarism is born, what it is meant in the French context of origin and how it acclimatized in Brazilian's intellectual experience, theoretically basing important diagnostics of our society. This is to conduct genetic mapping of a concept which is still strong in the horizon of the decisive clash between national projects that deal with Brazil's peripheral condition.

Existe no Brasil, segundo Sérgio Buarque de Holanda, um “vício de raciocínio”, que desfigura avaliações e desfavorece uma melhor compreensão das reais condições de mudança da sociedade brasileira. É em Raízes do Brasil que melhor se define esse “vício de raciocínio” como um “invencível desencanto em face das nossas condições reais”. Essa definição está apoiada na teoria do bovarismo - pouvoir qu`a l`homme de se concevoir autre qu`il n`est - teoria formulada por Jules de Gaultier (1858-1942), homme de lettres francês e divulgador de Nietzsche na França – a esse titulo, ele pretendeu-se filósofo –, que estende a caracterização do drama individual da personagem flaubertiana, Madame Bovary, para a caracterização das nações. Sérgio Buarque de Holanda não é o único autor que emprega essa noção, antes dele também encontramos o mesmo emprego em Paulo Prado e Lima Barreto, e muito depois dele em Celso Furtado e Paulo Eduardo Arantes, para ficar com os autores mais conhecidos. Este artigo visa rastrear algumas trajetórias da teoria do bovarismo, principalmente detectando seu significado no contexto literário francês de origem. Porém, o interesse aqui não é elucidar um problema francês, mas sim sugerir como uma “idéia transplantada” se aclimata na experiência intelectual brasileira, fundamentando teoricamente importantes diagnósticos de nossa sociedade. Trata-se de realizar o mapeamento genético de um conceito cuja atualidade ainda vibra forte no horizonte do embate decisivo entre projetos nacionais que lidam com a condição periférica do Brasil.
Keywords: bovarism; intelectual experience; Flaubert; Jules de Gaultier; Georges Palante; bovarismo; experiência intelectual; Flaubert; Jules de Gaultier; Georges Palante